Beyond Ear Discharge: Multisystem Langerhans Cell Histiocytosis with Temporal and Calvarial Involvement in a Child - Nadirah Rasyid Ridha; A Alfiah Mutmainnah; Martira Maddeppungeng (Alami Journal (Alauddin Islamic Medical) Journal, 2026)
Introduction: Langerhans cell histiocytosis (LCH) is a rare clonal myeloid neoplasm that commonly affects the bone and skin in children. Temporal bone involvement is uncommon and often mimics chronic otitis media, which may lead to delayed diagnosis. Case Presentation: We report a 4-year-5-month-old girl who presented with persistent right ear discharge and a visible mass in the external auditory canal for four months. Physical examination revealed diffuse papular and crusted lesions on the scalp and trunk, along with frequent nocturnal urination. The patient had a previous history of right ear tumor excision and parietal craniotomy. Histopathological analysis confirmed Langerhans cell histiocytosis, supported by positive S-100 immunohistochemical staining. Imaging demonstrated a soft-tissue mass obliterating the external ear canal and a parieto-occipital lesion with osseous destruction but no intracranial extension. The patient received vincristine and prednisone chemotherapy following the LCH-IV protocol, resulting in significant clinical improvement. Conclusion: Temporal bone LCH may clinically resemble chronic ear disease. Early recognition through biopsy and immunohistochemistry is crucial for establishing the diagnosis and initiating timely systemic therapy, thereby improving long-term outcomes.